Kajian Daya Dukung (Carrying Capacity) Lingkungan Perairan Pantai Pasir Putih Situbondo bagi Pengembangan Usaha Karamba Jaring Apung - Ida Adha Anrosana; Ariesia Ayuning Gemaputri (Jurnal Ilmiah Inovasi, 2017)
Sustainable sea cultivation has efficient features in resource use, productive and non-destructive environments. Under the Code of Conduct of Responsible Fisheries governing sustainable aquaculture development, it emphasizes the importance of a preliminary evaluation of the impact of aquaculture on genetic diversity, the integrity of the ecosystem, and the life of local communities (Sudrajat, 2008). This study was conducted with the main purpose of obtaining accurate information about the carrying capacity of the aquatic environment used for the development of floating net karamba business in the Pasir Putih Beach area of Situbondo Regency.Based on the results of research that has been done in Karamba Floating Net Pasir Putih Coastal Situbondo, it can be concluded that (1) The water quality in the aquatic environment in KJA area of Pasir Putih Beach Situbondo is still in accordance with the sea water quality standard of KepMen LH No. 51 of 2004 and considered feasible for the development of aquaculture activities in Karamba Floating Net.Â Keywords : Carrying Capacity, Karamba Floating Net